Pin chip : Kim Chu-yŏng changp'yŏn sosŏl. - Kim, Chu-yŏng, 1939- (Munhak Tongne, 2010)
Ŏjin grows up being lonely and abused by her mother who is angry or away looking for Ŏjin's father, who is a gambler on the run. After his death, Ŏjin leaves her own briefly married life and decides to look for her step sister, Sujin, whose address her father leaves before passing away. In the process, she comes to learn about the life of Sujin and Sujin's mother and also understands her own mother.